P. Krugman’s Core-Periphery Model. Case Study: The Tourist Demand on the Romanian Seaside (GeoPatterns, 2024)
Krugman's model is a new approach for Romania, even more applied to the Black Sea seaside. The tourist demand in such a way reveals the relations not only economic, but also of another nature between the core and the periphery. The data clearly show that this model is a forceful one, applicable not only to the Romanian seaside, but also to the region, country or continent, and its studycan reveal very interesting conclusions: the influence of the core on the periphery, how the North and the South interact in the chosen model and how seasonality affects seaside tourism.
Keywords: Krugman; core-periphery; tourist demand; seaside; seasonality